1987
DOI: 10.1159/000284493
|View full text |Cite
|
Sign up to set email alerts
|

On Organically Based Hallucinatory-Delusional Psychoses

Abstract: In an investigation of 70 chronically mentally ill patients in a district psychiatric hospital, 11 cases were discovered which had been diagnosed up to now as schizophrenia, but could now be diagnosed as being of organic origin. In group 1 (cases 1–6) there are dementive states after toxic, inflammatory or early childhood brain damage and familial epileptic malady with slowly progressive brain atrophy. They were easy to recognize clinically in their organic psychosyndromes, dementia, neurological symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A reason why other studies failed to replicate the findings of these authors may be that they did not broaden their scope to include other types of hallucination (Waters et al, 2014) and that the prevalence of MMHs has therefore been systematically underestimated. Secondly, the presence of hallucinations in other sensory modalities has traditionally led to non-psychiatric diagnoses (Waters et al, 2014) such as organic or neurological ones (Roberts, 1984;Albert, 1987). Another explanation may be that the CASH, apart from providing a systematic screening of hallucinations in four sensory modalities, has the advantage of describing their presentstate occurrence as well as their lifetime presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reason why other studies failed to replicate the findings of these authors may be that they did not broaden their scope to include other types of hallucination (Waters et al, 2014) and that the prevalence of MMHs has therefore been systematically underestimated. Secondly, the presence of hallucinations in other sensory modalities has traditionally led to non-psychiatric diagnoses (Waters et al, 2014) such as organic or neurological ones (Roberts, 1984;Albert, 1987). Another explanation may be that the CASH, apart from providing a systematic screening of hallucinations in four sensory modalities, has the advantage of describing their presentstate occurrence as well as their lifetime presence.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in a review (Waters et al, 2014) the nature of the relationship between hallucinations of different sensory modalities has hardly been examined. Although this situation is not unique for schizophrenia spectrum disorders (Waters et al, 2014), some studies indicate that the prevalence of multimodal hallucinations may be severely underestimated in this group (Goodwin et al, 1971) while others indicate that the presence of MMHs may be indicative of an underlying organic etiology (Roberts, 1984;Albert, 1987), or, in children and adolescents, of a more severe expression of schizophrenia (David et al, 2011;Jardri et al, 2014;Cachia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Is there any evidence in brain imaging studies that hallucinations, and especially AVHs, have a sensory basis [Shergill et al, 2000]? Why is it often so difficult for patients to report the acoustic characteristics of their voices -the owner of the voice [Nayani and David, 1996] and the voices' wording, tone, directions, strength [Albert, 1987] -and their physical features -location and ownership [Cutting, 1997]? Why is it so puzzling for them to place them in a Euclidean, intuitive geometric space?…”
Section: Towards a Definition Of Avhs As Disorders Of Self-consciousnessmentioning
confidence: 99%
“…The highly elabo rate way in which they are described and the patients' seeming indifference to their appar ently frightening nature have led some au thors to consider them examples of fantasy thinking rather than being truly hallucinatory. Other authors, however, have taken up an opposite position, and have suggested that this type of hallucination indicates an organic brain syndrome [7].…”
Section: Descriptive Termsmentioning
confidence: 99%
“…Bleuler further states that complex scenic hallucinations vivified by hal lucinations of other senses are restricted to acute twilight states, raising the possibility that these were cases of symptomatic schizo phrenia. Similarly Albert [7] described 11 cases of chronic psychoses, in which multi modal hallucinations were prominent, which were associated with evidence of organic brain damage. Reviewing the German litera ture Albert found that scenic hallucinations involving several modalities were particularly common in paranoid conditions following en cephalitis lethargica and had also been re ported in isolated cases of Huntington's cho rea, carbon monoxide poisoning and hypopi tuitarism.…”
Section: Clinical Conditionsmentioning
confidence: 99%